Transformasi Hisab-Rukyat Dalam Penentuan Awal Bulan Hijriah di Muhammadiyah - Ritonga, Marataon; Rakhmadi, Arwin Juli; Hidayat, Muhammad; Putraga, Hariyadi (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2024)
Muhammadiyah as a tajdid (renewal) movement will continue to improve the system in determining the beginning of hijri month through studies, discussions seminars, and research so that the methods and criteria used are truly following the Qur’an, hadith and the Muslims needs in the world. This research purpose to analyze, explore, and discover the transformation and changes in methods made by Muhammadiyah to determine the new month. The research method in this study is a literature study, by conducting a study and book analysis, journals, Suara Muhammadiyah magazines, and related references that have a close relationship with the studies. Based on the study, it shows that Muhammadiyah has made several transformations in its ijtihad to determine the beginning of the new hijri month, starting from the hisab imkanur rukyat sytem, then replaced with the hisab ijtima’ qabl al-ghurub, and the last one was perfected with the hisab wujudul hilal.